Coordinate hyperactivation of Notch1 and Ras/MAPK pathways correlates with poor patient survival: Novel therapeutic strategy for aggressive breast cancers - Mittal, Suruchi (Mol Cancer Ther, 2014)
Aberrant activation of Notch and Ras pathways has been detected in breast cancers. A synergy between these two pathways has also been shown in breast cell transformation in culture. Yet, the clinical relevance of Notch-Ras co-operation in breast cancer progression remains unexplored. In this study we show that coordinate hyperactivation of Notch1 and Ras/MAPK pathways in breast cancer patient specimens, as assessed by immunohistochemistry for cleaved-Notch1 and pErk1/2, respectively, correlated with early relapse to vital organs and poor overall survival. Interestingly, majority of such Notch1(high)Erk(high) cases encompassed the highly aggressive triple negative breast cancers (TNBC), and were enriched in stem-cell markers. We further show that combinatorial inhibition of Notch1 and Ras/MAPK pathways, using a novel monoclonal antibody against Notch1 and a MEK inhibitor, respectively, led to a significant reduction in proliferation and survival of breast cancer cells compared to individual inhibition. Combined inhibition also abrogated sphere-forming potential, and depleted the putative cancer stem-like cell subpopulation. Most importantly, combinatorial inhibition of Notch1 and Ras/MAPK pathways completely blocked tumor growth in a panel of breast cancer xenografts including the TNBCs. Thus, our study identifies coordinate hyperactivation of Notch1 and Ras/MAPK pathways as novel biomarkers for poor breast cancer outcome. Further, based on our preclinical data, we propose combinatorial targeting of these two pathways as a treatment strategy for highly aggressive breast cancers, particularly the TNBCs which currently lack any targeted therapeutic module.